New high elevation cockroach, Lamproblatta neuque sp. nov. (Dictyoptera: Lamproblattidae) from Colombia - Herrera, Melissa Sánchez; Martino, Frasella De; Sanabria, Pablo Emilio Realpe; Rebolledo, Emilio Realpe (Zootaxa, 2026)
We describe Lamproblatta neuque sp. nov., a new cockroach species from high-elevation forest patches ( 2600 m a.s.l.) near Bogotá, Colombia. This species is distinguished by a W-shaped ninth tergite, unique morphology of the subgenital and supra-anal plates, and the structure of the ootheca. Males also exhibit a small tergal gland on the supra-anal plate, expanding the known variation of this feature within Lamproblattidae. The discovery of L. neuque sp. nov. at an unusually high elevation highlights the persistence of biodiversity in remnant Andean forest habitats. Our findings underscore the need for a taxonomic revision of Lamproblattidae integrating morphological and genetic evidence.